Feasibility of photon-counting computed tomography as a novel imaging modality for challenging endodontic diagnostic tasks - Fontenele, Rocharles Cavalcante (2023)
Photon-counting computed tomography (PCCT) is an innovative technological advancement in relation to x-ray detectors which offers ultra-high-resolution images. The current study aimed to evaluate the visualization ability of PCCT compared to cone-beam computed tomographic (CBCT) devices for challenging endodontic diagnostic tasks. A reference image of an anthropomorphic phantom was acquired using an industrial micro-CT device. Thereafter, the phantom was scanned with three imaging devices, which included PCCT scanner (NAEOTOM Alpha) and two CBCT devices (3D Accuitomo 170 and NewTom VGi evo) having standard and high-resolution acquisition protocols. The diagnostic tasks involved visualizing fine endodontic structures (apical delta, narrow canal, and isthmus) and root cracks. Three experienced examiners assessed the images and were blinded to the PCCT and CBCT devices. Each image was rated according to a three-grade scale (appropriate, acceptable, or inappropriate) for the diagnostic tasks. In relation to fine endodontic structures grouped together, PCCT showed similar diagnostic performance compared to the reference image (p > 0.05). As for the CBCT devices, an excellent performance was only observed with the 3D Accuitomo 170 device at a high-resolution acquisition mode (p > 0.05). The visualization of root cracks was also better with 3D Accuitomo 170 compared to other devices (p < 0.05). Overall, PCCT and 3D Accuitomo 170 at a high-resolution setting showed similar performance for visualizing fine endodontic structures. In addition, the high-resolution CBCT protocol was superior for visualizing root cracks compared to both PCCT and other standard- and high-resolution CBCT protocols.